Mass communication in israel : nationalism, globalization, and segmentation - Soffer, Oren (Historian) (Berghahn Books, 2015)
Mass communication has long been recognized as an important contributor to national identity and nation building. This book examines the relationship between media and nationalism in Israel, arguing that, in comparison to other countries, the Israeli case is unique. It explores the roots and evolution of newspapers, journalism, radio, television, and the debut of the Internet on both the cultural and the institutional levels, and examines milestones in the socio-political development of Hebrew and Israeli mass communication. In evaluating the technological changes in the media, the book shows.